Green chemical engineering : an introduction to catalysis, kinetics, and chemical processes - Suresh, Sundaramurthy; Sundaramoorthy, S. (Boca Raton : CRC Press, Taylor & Francis Group, CRC Press is an imprint of the Taylor & Francis Group, an informa business, 2015)
'This book deals with energy and material balance applied to chemical reactors with catalysis to achieve a given purpose, including fundamentals of chemical reaction engineering. The authors explain reactor design fundamentals, from simple kinetic models to complex reactor systems involving heat/material transfer or multiple reaction contents. The book spans the full range from fundamentals of kinetics and heterogeneous catalysis via modern experimental and theoretical results of model studies to their equivalent large-scale industrial production processes. It also includes significant developments, with recent research case studies and literature. With a focus on practical application, rather than theory, the result is key knowledge for students at technical universities and professionals already working in industry.'--
Includes bibliographical references (pages 493-500) and index.
Keywords: Green chemistry